Peran Interaksi Teman Sebaya dalam Pembentukan Psikososial Siswa SD pada Waktu Istrahat - St. Hajar; Intan Dwi Hastuti (Universitas Muhammadiyah Mataram, 2026)
Peer interaction among primary school students is a natural social phenomenon, especially during break times, which provide students with the freedom to build relationships without academic pressure. Existing empirical studies have focused more on student interaction in the context of formal classroom learning, so that the spontaneous social dynamics and subjective experiences of students during break times have not been explored in depth. This study aims to examine the role of peer interaction in shaping the psychosocial development of primary school students during recess. The research used a qualitative approach with a descriptive design and was conducted at SD Inpres Nontotera, Bima Regency. Data were collected through participatory observation, in-depth interviews with the principal, classroom teachers, and students, as well as supporting documentation. Data analysis was conducted using the Miles and Huberman interactive model. The results showed that peer interactions contributed to the development of empathy, social skills, and emotional regulation.